Structural Associations of Academic Engagement and Spiritual Vitality with Academic Buoyancy: The Mediating Role of Self-Efficacy among Female Upper-Secondary School Students - Vaygani, Masoumeh; Khanmmohammadi Otaghsara, Arsalan; Mohammadzadeh Admolaee, Rajabali (Health Nexus, 2026)
This study examined a cross-sectional structural model linking academic engagement and spiritual vitality with academic buoyancy, directly and indirectly through self-efficacy, among female upper-secondary school students. A descriptive-correlational study was conducted with 350 students aged 15–18 years in Babol, Iran, during the 2024 academic year. Participants were selected through multistage cluster sampling. Academic buoyancy, academic engagement, spiritual vitality, and self-efficacy were assessed using self-report instruments. Structural equation modeling was performed in SPSS and AMOS. The proposed model showed acceptable fit (χ²/df = 1.45, RMSEA = .03, CFI = .98, NFI = .96, GFI = .96, and AGFI = .94). Academic engagement (β = .12, p = .02), spiritual vitality (β = .26, p = .001), and self-efficacy (β = .32, p = .001) were positively associated with academic buoyancy. Self-efficacy showed statistically significant indirect associations linking academic engagement (indirect β = .138, z = 2.84, p = .001) and spiritual vitality (indirect β = .09, p = .02) with academic buoyancy. Because the data were cross-sectional and self-reported, the findings do not establish temporal or causal effects.